A aprendizagem da docência sob a ótica dos estudantes de licenciatura em Educação Física no Programa Residência Pedagógica - Sims, Denise Souza (2020)
The teacher's work involves several types of expertise, requires extensive knowledge of the educational reality in which he / she performs his / her work, which involves initial training and experience in the professional field. However, research on teacher training has indicated the existence of a gap between the training process and the profession, and the need for a closer relationship between them. Within this context, some initiatives emerge with the assumption of valuing the approximation between the training period and professional performance, such as the Pedagogical Residence Program (PRP). Based on this, the objective of this work was to analyze how future Physical Education teachers conceive, perceive and mobilize the knowledge of teaching during the PRP. Qualitative research was characterized as a descriptive and explanatory case study. The techniques of data collection were questionnaire, observation and focus groups. Data analysis was done by content, which involved three stages of material exploration: data treatment, inference and interpretation. The analysis of the data allowed the creation of two categories: (1) University-School: teaching knowledge and professional training and (2) Learning to be a teacher. In the first category, given the perceptions and conceptions about the university-school relationship established by the social actors involved in the PRP, it was possible to identify the main difficulties encountered by residents; the contribution of this partnership to its formation; as well as the experiences mobilized by them in this teaching learning process, indicating how this structure can enhance professional teacher education, bringing it closer to the professional field. In the second category, based on the residents' learning, we can list the possible relationship with the pedagogical knowledge of the content; with curricular, disciplinary and training knowledge; as well as an experience of the practical knowledge of teaching, even in initial training. The work presented here brings some elements that show the potential that the PRP, linked to Supervised Curricular Internships, can promote for the professional training of teachers of Basic Education.